Vertebral Column Decancellation for Correcting Cervicothoracic Kyphotic Deformity in Patients With Ankylosing Spondylitis - Han Yu; Qi Wang; Yiming Fan; Dengbin Qi; Tianhao Wang; Bing Li; Yi Huang; Ze Wang; Chao Xue; Guoquan Zheng (Orthopaedic Surgery)
ABSTRACT Objective Surgery to correct the cervicothoracic kyphotic deformity in ankylosing spondylitis (AS) can be associated with serious neurovascular risks. According to the literature, there are no clinical reports documenting the use of vertebral column decancellation (VCD) in the treatment of cervicothoracic kyphotic deformity in patients with AS. The purpose of the present study was to retrospectively analyze and evaluate the effect of VCD on cervicothoracic kyphotic deformity in patients with AS. Methods Records of eight patients with cervicothoracic kyphotic deformity who underwent VCD at C7 in our institution were retrospectively reviewed. The mean duration of clinical follow‐up after surgery was 19 months. The cervical lordosis (CL) and C2–C7 sagittal vertical axis (SVA) were meticulously measured on full‐length spine radiographs. The chin‐brow vertical angle (CBVA) was measured on clinical photographs. Outcome measures utilized included the Neck Disability Index (NDI), the Japanese Orthopaedic Association (JOA) Score, and a Visual Analog Scale (VAS) for neck pain. The data analysis was performed using SPSS version 26.0 for Windows. For paired data adhering to a normal distribution, we utilized paired sample t‐tests to analyze preoperative and postoperative imaging parameters. Statistical significance was established at a p value threshold of < 0.01. Results All eight patients successfully completed the surgery. With an average VCD osteotomy angle of 47.6° ± 8.1° (±SD), the mean preoperative CBVA was 81.1° ± 17.6° (±SD), while the immediate postoperative value was 19.9° ± 5.7° (±SD). The overall average correction was 61.2° ± 18.9°. The mean preoperative cervical sagittal imbalance was 93.4 ± 27.3 mm (±SD), while the immediate postoperative value was 40.2 ± 18.9 mm (±SD). The overall average correction was 53.2 ± 28.1 mm. None of the eight patients experienced intraoperative complications, including nerve or vascular injury, cerebrospinal fluid leakage, or any other related complications. In the cohort of eight patients, the mean values for estimated blood loss, surgical time, and hospital stay were 1313 mL, 248 min, and 18 days, respectively. In comparison to preoperative scores, statistically significant improvement was noted in all patients in the postoperative period with regard to NDI, JOA, and VAS (p < 0.01, using a paired t‐test). Conclusion The VCD procedure proves to be a dependable and efficient approach for addressing cervicothoracic kyphotic deformities. It achieves remarkable corrections in cervical kyphosis and CBVA. Trial Registration Chinese Clinical Trial Registry: 2400090375